2013
DOI: 10.1021/mp3004034
|View full text |Cite
|
Sign up to set email alerts
|

Design and Biological Evaluation of Cell-Penetrating Peptide–Doxorubicin Conjugates as Prodrugs

Abstract: Doxorubicin (Dox) is a hydrophilic anticancer drug that has short retention time due to the efficient efflux in some cancer cells (e.g., ovarian adenocarcinoma SK-OV-3). Cyclic [W(RW)(4)] and the corresponding linear peptide (RW)(4) were conjugated with Dox through an appropriate linker to afford cyclic [W(RW)(4)]-Dox and linear (RW)(4)-Dox conjugates to enhance the cellular uptake and cellular retention of the parent drug for sustained anticancer activity. Comparative antiproliferative assays between covalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 40 publications
1
65
0
Order By: Relevance
“…Following receptor mediated endocytosis, bLf enters the endo-lysosome21 which could cause the cleavage of the drug from the protein due to the action of the digestive enzymes and the acidic environment leading to hydrolysis of covalent bond37. This results in nuclear Dox accumulation which was confirmed by reduced fluorescence of nuclear counterstain DAPI due to the competitive binding by Dox, proving our hypothesis that bLf-Dox leads to the increased retention of the drug.…”
Section: Discussionsupporting
confidence: 60%
“…Following receptor mediated endocytosis, bLf enters the endo-lysosome21 which could cause the cleavage of the drug from the protein due to the action of the digestive enzymes and the acidic environment leading to hydrolysis of covalent bond37. This results in nuclear Dox accumulation which was confirmed by reduced fluorescence of nuclear counterstain DAPI due to the competitive binding by Dox, proving our hypothesis that bLf-Dox leads to the increased retention of the drug.…”
Section: Discussionsupporting
confidence: 60%
“…49,50 Our findings showed that the cyclic nature of the peptide was a critical element in the self-assembly process and their biological activity possibly because of the constrained structure and different orientation of amino acids in their secondary structure.…”
Section: Peptide Nanostructuresmentioning
confidence: 74%
“…Although the final compound was obtained, purification was difficult because of its very low yield. Later, by adopting the procedure described by Nasrolahi Shirazi et al [30], we tried to synthesize the conjugate. However, in the preliminary step, attaching t-butyl anhydride to the C-terminal of compound 5 posed a problem.…”
Section: Resultsmentioning
confidence: 99%